(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study examines the patterns of interaction between the Franks and Muslims in the Levant during the Crusades, focusing on the concepts of convergence and divergence in political, economic, and cultural relations. The study demonstrates that political treaties played a pivotal role in regulating conflict and ensuring the continuation of daily life, particularly by providing safe passage for trade and tax collection, despite the fragility of these agreements and their frequent violations due to religious and political tensions. The study reveals that the individual motivations of some Franks, alongside economic interests, contributed to creating contradictory relationships between war and cooperation. Furthermore, the study highlights the importance of trade in shaping indirect relationships of convergence, as Italian merchants continued to trade with Muslims even during the Crusades, developing a professional identity that sometimes transcended religious affiliation. The study also indicates that daily life in coastal cities like Acre witnessed forms of spatial and economic coexistence, despite the persistence of religious and social distinctions. On the cultural front, the study examined means of communication such as gestures and the Arabic language, which helped bridge the gap in understanding during diplomacy. It also explored the impact of scientific exchange, particularly in the medical field, where the Franks benefited from Arabic and Greek medical knowledge and adopted systems such as physician licensing inspired by the Islamic system. Furthermore, medical accounts, such as those of Ibn Munqidh, revealed disparities in medical skills between the two sides, with instances of both success and failure. The study concludes that the relationship between the Franks and Muslims was neither pure conflict nor complete assimilation, but rather a mixture of convergence and divergence defined by religious identity and political and economic circumstances.